A microtubule-destabilizing kinesin motor regulates spindle length and anchoring in oocytes - Zou, Jianwei (The Rockefeller University Press, 2008)
The kinesin-13 motor, KLP10A, destabilizes microtubules at their minus ends in mitosis and binds to polymerizing plus ends in interphase, regulating spindle and microtubule dynamics. Little is known about kinesin-13 motors in meiosis. In this study, we report that KLP10A localizes to the unusual pole bodies of anastral Drosophila melanogaster oocyte meiosis I spindles as well as spindle fibers, centromeres, and cortical microtubules. We frequently observe the pole bodies attached to cortical microtubules, indicating that KLP10A could mediate spindle anchoring to the cortex via cortical microtubules. Oocytes treated with drugs that suppress microtubule dynamics exhibit spindles that are reoriented more vertically to the cortex than untreated controls. A dominant-negative klp10A mutant shows both reoriented and shorter oocyte spindles, implying that, unexpectedly, KLP10A may stabilize rather than destabilize microtubules, regulating spindle length and positioning the oocyte spindle. By altering microtubule dynamics, KLP10A could promote spindle reorientation upon oocyte activation.